استخدام الفن في الدعوة إلى الله: الشيخ سنان بونانغ نموذجا: The use of art in the Islamic’s advocacy: the advocacy method of Sheikh Sunan Bonang as a model - Balki, Nur Nazwan; Ahmad H. Osman, Rahmah; Mohd Mahzan, Iwana Fatini (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص العمل الدعوي يقوم بعملية تبليغ المفاهم الإلهية للمسلمين وغير المسلمين سائرا بما حدده الإسلام وارتضاه الله تعالى. ويحرص العلماء على تنويع الإستراتيجيات والأساليب في انتشار الدعوة من أجل اقناع المدعو به. لذلك يقوم الشيخ سنان بونانغSunan Bonang وهو واحد من أهم رواد الإسلام في جاوة باختيار الفن بوصفه طريقة لتبليغ الدعوة الإسلامية كما أن الفن يعتبر إحدى الوسائل القريبة لقلوب الجاويين. وسيعرض هذا البحث نبذة عن الشيخ سنان بونانغ وإساهمته في الدعوة الإسلامية، ثم تقوم الباحثة بالتوضيح عن الطريقة الفنية التي يستخدمها الشيخ سنان بونانغ في دعوته إلى الله. ومنهج البحث الذي تستخدمه الباحثة لجمع البيانات من خلال الدراسة الوصفية التحليلية أي بطريقة قراءة الكتب. وتظهر النتائج أن الشيخ سونان بونانغ يستخدم العناصر الفنية مثل خيال الظل Wayang Kulit والموسيقى التقليدية الجاوية بوصفها وسيلة فعالة لتبليغ الدعوة و تعليم القيم الإسلامية للجاويين .وهذا يعني بأن الدعوة على الأساس لا تتم فقط شفهيًا، بل أيضًا مع مراعاة جميع الظروف، على سبيل المثال، من خلال التأثير الثقافي الناتج عن أداء خيال الظل حيث كانت القصة المقدمة للمستمع وهي تصورا عن الفروق الدقيقة في الإسلام. Abstract The advocacy is a movement in informing the Muslim and the non-Muslim to understand the concept of divinity outlined by Islam and approved by God Almighty. Strategies and methods of advocacy should be diversified to attract the attention of the target.Therefore, Sunan Bonang, a pioneer of Islam in Java has chosen art as a method to spread the Islamic’s advocacy because art is a platform that is close to the hearts of the Javanese people.This study will be described about the biodata of Syeikh Sunan Bonang and his contribution in spreading the supplication of Islam.Other than that, the researcher also clarifies the art used by Sheikh Sunan Bonang in order to spread an Islamic’s advocacy. The method used by the researcher to collect data is by an analytical descriptive study. The results of this study found that Sheikh Sunan Bonang uses artistic elements such as wayang kulit and Javanese traditional music as an effective medium of preaching to teach Islamic values to the Javanese community.